(untitled) (Ustozlar uchun, 2026)
This article scientifically examines the automation of the heating, ventilation, and air conditioning (HVAC) system of an administrative building. Problem: under conventional thermostat-based control, room temperatures fluctuate within ±2.5°C, and 32–38% of energy consumption is wasted heating/cooling unoccupied rooms. Method: a centralized Building Management System (BMS) was developed based on Siemens Desigo PXC controllers, temperature/CO₂/humidity sensors, and variable air volume (VAV) dampers; occupancy-based scheduling and cascade PID control were applied. Result: temperature was maintained at ±0.5°C accuracy and CO₂ levels were kept within 800–1000 ppm. Conclusion: annual energy consumption decreased by 27.6%, heating/cooling costs dropped from 124,600 to 90,200 thousand UZS, and occupant comfort (PMV index) improved significantly.